Anterior temporal lobectomy. A cross-sectional observational study of potential surgical candidates at a single institute - Soni, Aayesha (Department of Medicine, 2025)
Background: Epilepsy is a common neurological disorder, associated with serious cognitive and psychosocial burdens, especially when poorly controlled. Mesial temporal lobe epilepsy (mTLE) is the most common form of human focal epilepsy. It is often refractory to antiepileptic drugs, and the most amenable to surgical treatment which often renders patients seizure free. Furthermore, surgery for mTLE has low procedural risk, is cost-effective and best performed early in the disease course for maximal benefit. It is surprising, therefore, that mTLE surgery remains widely under-utilised, in both well and poorly resourced settings. Objectives: The aim of this study was to establish the frequency of occurrence of patients with electroencephalographic epileptiform discharges consistent with mTLE attending a neurophysiology laboratory at a tertiary hospital in South Africa, and determine whether these patients may be candidates for anterior temporal lobectomy, the most commonly performed surgery for mTLE. Methods: This was a quantitative audit of all scalp electroencephalograms (EEG) performed at the Groote Schuur Neurophysiology laboratory during the period January 1st 2017 to December 31st 2019. Where CT and MRI brain scans had been performed, these were assessed for corroborative evidence of mTLE. Results: Over the three-year period, 4 342 EEGs were assessed. A total of 411 (11%) showed epileptiform discharges consistent with all epilepsy types. Of these, 327 (69%) were of focal onset and 108 (2% of the total number of EEGs performed) were consistent with mTLE. Of the patients with electroencephalographic features of mTLE, only 27 (25%) had had MRI brain scans performed according to an epilepsy surgery protocol. Of these, 6 exhibited MRI findings confirming mTLE, identifying them as potential surgical candidates. Over three years, 75% of patients with electroencephalographic evidence suggesting mTLE did not receive appropriate work-up for epilepsy surgery. Conclusion: Surgery, especially anterior temporal lobectomy, is widely acknowledged to be an efficacious and cost-effective intervention in patients with medically refractory mTLE. The findings of our study suggest that patients with mTLE are under-investigated for potential surgical management, and that epilepsy surgery is under-utilised in South Africa. These findings are in line with similar studies in both well-resourced and resourceconstrained countries. We hope that our study will highlight the utility of EEG as a screening tool to identify patients with drug-resistant epilepsy due to mTLE, who may be candidates for anterior temporal lobectomy.